2022
DOI: 10.1029/2022jd037138
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Scale Resolved Surface Fluxes Across a Heterogeneous, Mid‐Latitude Forested Landscape

Abstract: The Earth's surface is heterogeneous at multiple scales owing to spatial variability in various properties. The atmospheric responses to these heterogeneities through fluxes of energy, water, carbon, and other scalars are scale‐dependent and nonlinear. Although these exchanges can be measured using the eddy covariance technique, widely used tower‐based measurement approaches suffer from spectral losses in lower frequencies when using typical averaging times. However, spatially resolved measurements such as air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 108 publications
(204 reference statements)
1
32
0
Order By: Relevance
“…We also had little basis for estimating bias errors including potential underestimation of LE due to the known challenges of lack of energy balance closure of EC measurements (Foken, 2008; Leuning et al., 2012; Stoy et al., 2013) that the CHEESEHEAD19 experiment as a whole is designed in part to address (Butterworth et al., 2021). However, independent approaches are converging on the notion that underestimated turbulent flux terms may be due more to sensible than latent heat fluxes (Charuchittipan et al., 2014; Gerken et al., 2018; Mauder et al., 2020; Paleri et al., 2022). Ongoing efforts to parameterize underestimated turbulent fluxes require estimates of atmospheric boundary layer heights (Mauder et al., 2021), which are difficult to quantify using individual flux towers, but the extensive land surface and atmospheric observations available from CHEESEHEAD19 (Butterworth et al., 2021) provide opportunities to better‐understand potential bias uncertainties in EC measurements due to mesoscale atmospheric motions.…”
Section: Discussionmentioning
confidence: 99%
“…We also had little basis for estimating bias errors including potential underestimation of LE due to the known challenges of lack of energy balance closure of EC measurements (Foken, 2008; Leuning et al., 2012; Stoy et al., 2013) that the CHEESEHEAD19 experiment as a whole is designed in part to address (Butterworth et al., 2021). However, independent approaches are converging on the notion that underestimated turbulent flux terms may be due more to sensible than latent heat fluxes (Charuchittipan et al., 2014; Gerken et al., 2018; Mauder et al., 2020; Paleri et al., 2022). Ongoing efforts to parameterize underestimated turbulent fluxes require estimates of atmospheric boundary layer heights (Mauder et al., 2021), which are difficult to quantify using individual flux towers, but the extensive land surface and atmospheric observations available from CHEESEHEAD19 (Butterworth et al., 2021) provide opportunities to better‐understand potential bias uncertainties in EC measurements due to mesoscale atmospheric motions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous modeling studies have suggested that both fluxes are about equally affected (Mauder et al., 2013; Twine et al., 2000) in relative terms (i.e., the Bowen ratio is preserved) or that the sensible heat flux is about twice as much affected (Charuchittipan et al., 2014; Roo et al., 2018), depending on modeling assumptions. Solving this puzzle will need further studies taking into account the effect of dispersive fluxes generated by sub‐mesoscale circulations, either from large‐eddy simulations (Roo et al., 2018; Wanner et al., 2022) or spatially resolving turbulence measurements (Mauder et al., 2010; Paleri et al., 2022). In addition, lysimeters (which typically provide estimates of evapotranspiration on scales smaller than a flux tower) and balloon soundings (which measured temperature and humidity can be used to estimate H and LE for the vertical profile), can also provide independent reference measurements if they are representative of the flux tower footprint (e.g., Gebler et al., 2015; Mauder et al., 2018; Widmoser & Wohlfahrt, 2018; Wouters et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al, 2023). However, the wavelet technique can be used to analyze nonstationary data with contributions from different frequencies, especially airborne measurements that span non-homogenous regions (Desjardins et al, 1995;Mauder et al, 2007;Paleri et al, 2022;Torrence & Compo, 1998). Mauder et al (2007) found that the differences in LE estimations between the EC and wavelet techniques are less than 2%.…”
Section: 1029/2023jd039586mentioning
confidence: 99%
“…The wavelet method permits to allocate the information about flux contributions from the entire flight track to a specific subsegment of that track. We apply wavelet calculation to the same flight track of Figure 3 in Paleri et al (2022) for comparison and to ensure consistent calculation (Figure 2). The wavelet technique is applied to calculate the wavelet power co-spectrum of LE (LE WT ), and the wavelet power spectra of w and r v (Figures 2a-2c).…”
Section: Example Of Wavelet Variance and Covariancementioning
confidence: 99%